An Appraisal of the Principal Concerns and Controlling Factors for Arsenic Contamination in Chile - Alam-, M (Nature Research, 2023)
Although geogenic Arsenic (As) contamination is well-recognized in northern Chile, it is not restricted to this part of the country, as the geological conditions favoring As release to the human environment exist across the country as well, although not at the same level, based on comparatively fewer studies in central and southern Chile. The present work provides a critical evaluation of As sources, pathways, and controls with reports and case studies from across the country based on an exhaustive bibliographic review of its reported geogenic sources and processes that affect its occurrence, systematization, and critical revision of this information. Arc magmatism and associated geothermal activities, identified as the primary As sources, are present across the Chilean Andes, except for the Pampean Flat Slab and Patagonian Volcanic Gap. Metal sulfide ore zones, extending from the country’s far north to the south-central part, are the second most important geogenic As source. While natural leaching of As-rich mineral deposits contaminates the water in contact, associated mining, and metallurgical activities result in additional As release into the human environment through mining waste and tailings. Moreover, crustal thickness has been suggested as a principal controlling factor for As release, whose southward decrease has been correlated with lower As values. © 2023, The Author(s).